Exploring the complex dynamics of BMI, age, and physiological indicators in early adolescents - Ning Ding; Suyun Li; Han Zhou; Zhenchuang Tang; Tianlin Gao; Meina Tian; Changqing Liu; Xiaoyan Luo; Hongtong Chen; Lianlong Yu; Yao Chen; Li Yang; et al. (BMC, 2024)
Abstract Background and objectives To investigate the relationship between body mass index (BMI) and blood biochemical indicators in early adolescence, and to provide ideas for early prevention of diseases and explore possible disease-related predictors. Methods 3125 participants aged 10 ∼ 14 years were selected from China from the survey of "China Nutrition and Health Surveillance ( 2016 ∼ 2017 ) ". Employing advanced statistical methods, including generalized linear models, heatmaps, hierarchical clustering, and generalized additive models, the study delved into the associations between BMI and various biochemical indicators. Results In early adolescence, indicators including systolic pressure, diastolic pressure, weight, height, BMI, hemoglobin, blood uric acid, serum creatinine, albumin, vitamin A presented increasing trends with the increase of age ( P < 0.05 ), whereas LDL-C, vitamin D, and ferritin showed decreasing trends with the increase of age ( P < 0.05 ). The increase in hemoglobin and blood uric acid levels with age was more pronounced in males compared to females ( P < 0.05 ). BMI was positively correlated with blood glucose, hemoglobin, triglyceride, LDL-C, blood uric acid, serum creatinine, ferritin, transferrin receptor, hs-CRP, total protein, vitamin A ( P < 0.05 ). There was a significant BMI × age interaction in the correlation analysis with LDL-C, transferrin receptor, serum creatinine, and hs-CRP ( P < 0.05 ). BMI was a risk factor for hypertension, hypertriglyceridemia, low high density lipoprotein cholesterolemia, and metabolic syndrome in all age groups ( OR > 1, P < 0.05 ). Conclusions High BMI was a risk factor for hypertension, hypertriglyceridemia, low high density lipoprotein cholesterolemia, and MetS in early adolescents. With the focus on energy intake beginning in early adolescence, the maintenance of a healthy weight warrants greater attention.